ANALISIS GEMA INTERTEKSTUAL TERHADAP AMSAL 8 (17) DAN YOHANES 14 (21) - Piter, Romanus (Aggiornamento, 2024)
The intertextual echo analysis of John 14:21 and Proverbs 8:17 is the earliest exposition in biblical studies. This analysis is based on the author's interest after seeing that these two texts have similarities or similarities. In biblical studies, these similarities or similarities need to be studied in depth in order to understand the hidden meaning behind them. The intertextual echo analysis method is used to see this meaning and make it relevant in the life of faith. This analysis finds that "loving wisdom will be loved by wisdom" in Proverbs 8:17 is correlated with "loving Jesus will be loved by Jesus". People who have wisdom are the same as believers. In the practical realm of living faith in Jesus, seeking and loving wisdom is evident in waiting for the coming of the Holy Spirit at Pentecost. It is in this context that the wisdom in Proverbs finds its echo in the Catholic Church's celebration of faith, especially at Pentecost.